Fair governance paternalism and perfectionism - Buckley, F. H. (Francis H.), 1948- (Oxford : Oxford University Press, 2009)
This is a study of legal interference with individual preferences and will canvass the interdisciplinary literature in economics, psychology, philosophy, and law. It discusses the particular conditions necessary for the state to legally interfere with our freedom of choice.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Paternalism; Akrasia; Perfectionism (Personality trait)